The monkey and the dove : and four other true stories of animal friendships - Holland, Jennifer S.; Holland, Jennifer S. (New York : Workman Pub., 2012)
Presents five stories about animals who have forged unlikely, abiding bonds with other animals of different species, from the rhesus monkey and the white dove to the lion and the baby oryx.
The monkey and the dove -- The bear and the cat -- The elephant and the dog -- The dog and the cat -- The lion and the oryx.
Stories adapted from: Unlikely friendships. 2011.
For ages 7 and up.
Keywords: Social behavior in animals -- Juvenile literature; Animals -- Juvenile literature; Friendship -- Juvenile literature; Social behavior in animals; Animals; Friendship